METHODS OF DEVELOPMENT OF OPERATIONS OF COMMERCIAL BANKS IN THE FUND MARKET - Mardonov Shaxriyor Xolmirzo o‘g‘li (American Journals, 2023)
In this article, the set of economic relations related to the organization of operational activities of banks in the stock market was chosen as the subject of research. The object of research is to calculate the sum of mechanisms for organizing the operational activity of banks as an issuer, investor or investment institution in the stock market, and the object of research taken as commercial banks. Also, in the article, the opinions of foreign and local scientists on this topic are highlighted and suggestions are made.
Keywords: bank, stock market, capital market, investor, capitalization, depositor, issuer, share, bond, joint stock company.